Formas de uso e conservação do butiazeiro (Butia odorata Barb. Rodr.) Noblick & Lorenzi em unidades de produção de Santa Vitória do Palmar (RS) - Piaia, Angelo (2013)
Considering the problem of the depletion of nonrenewable resources and today s environmental impacts, especially the reduction of biodiversity, the debates about the need for environmental sustainability have increased, making it essential to consider all areas, promoting dialogue and alternatives to traditional models of production. In this context, understanding the knowledge of farmers on ways to take advantage of native fruits presents itself as a viable alternative and raises the analysis of various uses of the Pindo Palm in order to verify how they can influence in the continuation of this native tree of Rio Grande do Sul. The objective of this research was to understand how the different uses of the Pindo Palm (Butia odorata), in the social context of production units of Santa Vitória do Palmar (RS), can influence its management and preservation of this species, as well as to assist in the sustainability of palms ecosystem. For this study, it was chosen as method of approach the literature review on the topic, the collection of local data with questionnaires and semi-structures interviews with farmers, technicians and craftsmen, as well as photographic records relating forms of conservation and use of the Pindo Palm. Based on the analysis of the reports of farmers from Santa Vitória do Palmar it is possible to state that the ways of using the Pindo Palm have influence on its preservation, as farm families are aware of their importance, be it for their own food or for the conservation of the plant itself. In addition, the different uses of the Pindo Palm are linked to economic, socio-cultural and ecological dimensions, with a strong emphasis on the socio-cultural one. And finally, what is most important in the speeches of farmers is the affective bond between people and the Pindo Palm, showing a strong relationship of belonging and protection of this native species.